2002
DOI: 10.1152/jn.2002.87.6.2770
|View full text |Cite
|
Sign up to set email alerts
|

Protein Synthesis Is Required for the Enhancement of Long-Term Potentiation and Long-Term Memory by Spaced Training

Abstract: Spaced training is generally more effective than massed training for learning and memory, but the molecular mechanisms underlying this trial spacing effect remain poorly characterized. One potential molecular basis for the trial spacing effect is the differential modulation, by distinct temporal patterns of neuronal activity, of protein synthesis-dependent processes that contribute to the expression of specific forms of synaptic plasticity in the mammalian brain. Long-term potentiation (LTP) is a type of synap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
146
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 189 publications
(156 citation statements)
references
References 37 publications
9
146
0
1
Order By: Relevance
“…The spacing effect requires new protein synthesis (14,40). In addition, a recent study has shown that the blockade of protein synthesis in the Fl with anisomycin abolished HOKR adaptation during spaced but not massed training (12).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The spacing effect requires new protein synthesis (14,40). In addition, a recent study has shown that the blockade of protein synthesis in the Fl with anisomycin abolished HOKR adaptation during spaced but not massed training (12).…”
Section: Discussionmentioning
confidence: 99%
“…We further explored the structural basis of differential memory retention with distinct intervals and examined the correlation between the number of PF-PC synapses and the retention of HOKR gain on day 2. The density of these synapses in the superficial molecular layer of the middle part of the Fl and the adjacent Pfl was measured using the unbiased physical dissector method in M, S 40 , and S 60 mice (Fig. 4).…”
Section: Memory Retention Is Strongly Correlated With Reductions In Pmentioning
confidence: 99%
See 1 more Smart Citation
“…In rabbit eyeblink conditioning, infusions of anisomycin into the cerebellar interpositus nuclei depress both the acquisition and retention of the conditioned response (Bracha et al, 1998;Gomi et al, 1999). The role of protein synthesis has been suggested in the memory acquisition induced by the spaced training in the conditioning of the proboscis extension reflex of honey bees (Menzel et al, 2001) and in the contextual learning of fear conditioning in rats (Scharf et al, 2002).…”
Section: Role Of Protein Synthesis In Memory Transfermentioning
confidence: 99%
“…In Drosophila, training with spaced trials extends the memory, which depends on cAMPresponsive element-binding protein (CREB) and protein synthesis (Yin et al 1995). Others find that spaced tetanic stimulation induces a more persistent expression of LTP (Scharf et al 2002) and that the consequences of spaced application of serotonin in Aplysia is more profound than when massed (Mauelshagen et al 1998). Overall, it seems likely that prolonged increase in cell excitability and/or a more refined pattern of activation over time leads to the increase in cell survival in response to learning.…”
Section: Cold Spring Harbor Laboratory Press On May 11 2018 -Publishmentioning
confidence: 99%